More than 15 million people work as ‘volunteers’ for the European Economic Community (Journal of Parents and Teachers, 2026)
In February 1986, the United Nations General Assembly declared 5 December as the ‘International Volunteer Day for Economic and Social Development’. Volunteering has a long tradition in Europe. In Spain, it seems that the time has also come for volunteer associations. Currently, there are nearly half a million people who share their time in voluntary service to marginalised sectors of society. Volunteering mobilises everyone from 15-year-olds to 70-year-old women. Social volunteering is a new way of life.
Keywords: social volunteering, European Community, Spain, Associations